A rare case of acute non-puerperal uterine inversion due to large leiomyoma in COVID pandemic: challenges in clinical diagnosis and management - Murde, Snehal G.; Raut, Rohini R.; Kumari, Beena; Hojai, Dinesh C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Non puerperal uterine inversion is a very rare clinical scenario with very few gynaecologist actually managing it in their lifetime. Acute variety of non-puerperal inversion is even rarer and thus possess diagnostic and management challenges. Case study of a rare case of a 45 years old female who was admitted for an elective surgery and had sudden acute inversion of uterus which was clinically diagnosed. Patient was managed by debulking of tumour which turned out to be large leiomyoma, followed by total abdominal hysterectomy. Rarity of the disease, atypical symptoms and less clinical exposure to such cases pose diagnostic as well as surgical challenges as in our case.